MODERN STRUCTURE OF THE RUSSIAN AIRPORT INDUSTRY (ON THE EXAMPLE OF THE CENTRAL AND NORTH-WEST FEDERAL DISTRICTS) - A. A. Titov; A. Yu. Yakovlev (Вестник университета)
The existing organizational and legal forms, forms of ownership and the main types of economic activity of such subjects of economic relations in the transport sector as airports have been analysed. The airport infrastructure management in accordance with the Air Code of the Russian Federation is imposed on the operator (air operator), which is a specific legal entity. It can be of various organizational and legal form and form of ownership and also is able to carry out various types of economic activity. Airports of federal significance in the Central and North-West Federal districts have been examined in the article.. Among the legal entities under study can be distinguished such organizational and legal forms as: budgetary institution, state-owned enterprise, business companies (public, non-public joint-stock companies and limited liability companies) of the following forms of ownership: private, mixed and state (federal and owned by the constituent entities of the Russian Federation). The most common among organizational and legal entities are business entities in the form of a non-public joint-stock company and limited liability company. Among the forms of ownership, the most common form is the ownership of the Russian regions. Among forms of ownership, the most common form is the ownership of the constituent entities of the Russian Federation. A significant part is accounted for by business entities with 100 % of their participation.